Pen injected apomorphine against off phenomena in late Parkinson's disease: a double blind, placebo controlled study. Issue 6 (June 1995) - Ostergaard, L; Werdelin, L; Odin, P; Lindvall, O; Dupont, E; Christensen, P B; Boisen, E; Jensen, N B; Ingwersen, S H; Schmiegelow, M
Abstract : The effect, therapeutic dose range, and pharmacokinetics of apomorphine, given as subcutaneous injections by a single use pen, were evaluated in the treatment of off phenomena in 22 patients with idiopathic Parkinson's disease. At study entry a placebo controlled apomorphine test was performed, and apomorphine doses were then individually titrated (mean 3.4 (range 0.8-6.0) mg) and compared with placebo in a double blind cross over phase. With apomorphine compared with placebo the mean daily duration of off periods was reduced by 51% as assessed by the patients and by 58% as assessed by the staff. The severity of off periods was also significantly reduced. The effect was unchanged after a maintenance phase of eight weeks. At study termination 13 of 14 patients were able to inject themselves and 11 of 14 patients found that their feeling of freedom had increased. The most common adverse events were nausea, subcutaneous nodules, and increased frequency of involuntary movements. Pharmacokinetics were linear and did not change with repeat dosing. The tmax ranged from five to 45 minutes (16 patients). It is concluded that pen injected apomorphine is a valuable treatment for patients with advanced Parkinson's disease with on-off phenomena.